2016
DOI: 10.1111/ijd.13282
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in the research about Propionibacterium acnes strain diversity and acne: pathogen or bystander?

Abstract: Recent progress has steadily reported the existence of the diverse strains of Propionibacterium acnes, and these studies have contributed to the elucidation of their contradictory roles between normal commensals and pathogens. In this review, the authors aimed to provide an update on the recent understanding of research about P. acnes strain diversity and acne, analyzing the potential implications for clinical applications. Before the era of genomic research, P. acnes was known to be distinguished based on ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 88 publications
0
20
0
Order By: Relevance
“…Phylogenic studies also showed that acquired DNA sequences and bacterial immune elements may have roles in determining virulence properties of C. acnes strains. Moreover, biochemical, transcriptomic and proteomic analyses demonstrated that C. acnes phylotypes exhibit differences in inflammatory potential and expression of various putative virulence factors that may explain their distinct involvement in acne disease . These factors include neuraminidase, lipase, polyunsaturated fatty acid isomerase, the iron acquisition protein HtaA (a highly immunoreactive cell surface antigen) and heat shock proteins (HSP20, DnaK, DnaJ, GrpE and GroEL) .…”
Section: Acnes Phylotypes and Virulencementioning
confidence: 99%
See 1 more Smart Citation
“…Phylogenic studies also showed that acquired DNA sequences and bacterial immune elements may have roles in determining virulence properties of C. acnes strains. Moreover, biochemical, transcriptomic and proteomic analyses demonstrated that C. acnes phylotypes exhibit differences in inflammatory potential and expression of various putative virulence factors that may explain their distinct involvement in acne disease . These factors include neuraminidase, lipase, polyunsaturated fatty acid isomerase, the iron acquisition protein HtaA (a highly immunoreactive cell surface antigen) and heat shock proteins (HSP20, DnaK, DnaJ, GrpE and GroEL) .…”
Section: Acnes Phylotypes and Virulencementioning
confidence: 99%
“…Moreover, biochemical, transcriptomic and proteomic analyses demonstrated that C. acnes phylotypes exhibit differences in inflammatory potential and expression of various putative virulence factors that may explain their distinct involvement in acne disease. 40,42 These factors include neuraminidase, lipase, polyunsaturated fatty acid isomerase, the iron acquisition protein HtaA (a highly immunoreactive cell surface antigen) and heat shock proteins (HSP20, DnaK, DnaJ, GrpE and GroEL). 3 Host-interacting factors, such as CAMP factors, hemolysins and dermatan sulphate-binding adhesins (DsA1 and DsA2) have also been identified as possible pathogenic factors.…”
Section: Acnes Phylotypes and Virulencementioning
confidence: 99%
“…Microbial dysbiosis of C. acnes , Malassezia , bacteriophages, and perhaps other microbes, coupled with disturbed skin barrier formation and immune responses, are all factors correlated with acne . A recent metagenomic study that compared acne skin with healthy skin revealed that the balance among bacterial, fungal and bacteriophage components was important in the maintenance of skin health . Microbial dysbiosis can influence innate immunity through multiple targets, which include peroxisome proliferator‐activated receptors, interferon signalling, tumour necrosis factor activation, ILs and Toll‐like receptors.…”
Section: Microbial Dysbiosis In Acnementioning
confidence: 99%
“…43,61,62 A recent metagenomic study that compared acne skin with healthy skin revealed that the balance among bacterial, fungal and bacteriophage components was important in the maintenance of skin health. 11,66 Microbial dysbiosis can influence innate immunity through multiple targets, which include peroxisome proliferator-activated receptors, interferon signalling, tumour necrosis factor activation, ILs and Toll-like receptors. Matrix metalloprotease activity, being one of the factors of innate immunity response to C. acnes, has also been proposed as a cause of hyperkeratinization in pilosebaceous units, which is important for acne pathogenesis.…”
Section: Microbial Dysbiosis In Acnementioning
confidence: 99%
“…The role of P. acnes is not clear, as this bacterium is ubiquitous. However, certain strains of acne may be more associated with acne and be pro-inflammatory [4,5,6]. Regardless of the ongoing debate regarding P. acnes , antibiotics used in the treatment of acne appear to have anti-inflammatory effects independent of their antimicrobial effects [7,8,9].…”
Section: Introductionmentioning
confidence: 99%